Physical Education and sport in Brazil: graduation process and professional action perspectives - Jair Sindra Virtuoso Junior; Lísia Costa Golçalves de Araújo; Rodrigo Flores Sartori; Juarez Vieira do Nascimento (Journal of Physical Education (Maringá), 2008)
Considering the professional graduation process, the physical education is characterized as a field of contradictory tendencies, addressed for the maintenance and reproduction of the traditional patterns of values, assuming the tendency of promoting changes at the same time. With the attempt of contributing to the discussion on the new curricular guidelines, and based on the specialized literature on some emergent epistemological conceptions in the area, this study aimed at analyzing the tendencies concerning the professional graduation process and intervention, identified in the curriculum of the graduation courses at Physical Education. It is interesting to make evident that the curricula of the Physical Education courses have been elaborated based on the autonomy granted to the institutions by the Resolution nº 03/CES/CNE/1987. This autonomy is also supported by the lack of agreement among the Physical Education professionals in what concerns both the definition of the investigation field and the object studied. Therefore, the adaptation of the graduation process so that the professional can act in a satisfactory way considering the multiple sub-fields of intervention has been inevitable, due to time limitations established to the initial graduation process, as well as to the desire of each institution in the sense of emphasizing a certain area, according to the professional profile wanted. The discussions accomplished in this study lead us to emergent themes related to the Physical Education different perspectives that contemplate both the interdisciplinarity and the professional graduation process overcoming, as well as the specialist x global graduation dichotomy. They will also contribute with the review of the speeches related to some aspects, such as the body, the sport-product, and the industry of leisure.